Using Muslims Mannerism and Habits (UMMAH): An Early Warning Strategy for Countering Violent Extremism - Mamud, Yusuf Abubakar; Agyeno, Oboshi J (European Scientific Journal, ESJ, 2017)
The fight against terrorism has long relied on military intervention and hard power strategy to curb terror threats. Current reality and the spade at which youths who are radicalized under the banner of religion to carry out terrorist activities has called for more attention paid on alternative counterterrorism (CT) measures and policies. CT initiatives should be broadened to accommodate soft power approach that interrupts the radicalization and recruitment of civilians into violent extremism and terrorism. It is revealed that more terrorist actions and violent extremism had been undertaking by youths that professed the Islamic faith more than any in the 21st century. The worrisome trend has called the development of UMMAH as a CT strategy to understand the narratives and messaging exploited by recruiters and facilitators of violent extremism as a religious obligation. The strategy demands a counter narrative and messages that would replace the message of hate, violence and bigotry, with love, peace, tolerance and coexistence.